Respons Pertumbuhan Planlet Anggrek Phalaenopsis terhadap Pemberian BA dan NAA Selama Aklimatisasi - Arianbach, Achmad Fatih; Saputra, Herry Marta; Zasari, Maera (JURNAL AGROTROPIKA, 2023)
Orchid plants are a type of plant that belongs to the Orchidaceae family which has approximately 900 genera and estimated to have 15.000- 25.000 species. Orchid plants can be cultivated vegetative and generative. Tissue culture is one of the vegetative propagation methods of orchids. Acclimatization is a critical period for tissue cultured plantlets. Acclimatization is a critical period for plantlets resulting from tissue culture. Plant growth regulators can help stimulate plantlet growth during the acclimatization period. growth regulators is one of the success factors in acclimatization. This study aims to determine the best BA and NAA concentrations and the best treatment combination for acclimatization of Phalaenopsis orchids. This research was conducted from March to July 2022 at the Research and Experimental station, University of Bangka Belitung. This study used a factorial randomized block design (RBD). The factors tested were the concentrations of BA and NAA solutions. The results showed that the acclimatization of Phalaenopsis orchids was successful, indicated by the high percentage of plantlet survival. The highest average growth was shown at concentrations of 10 ppm BA and 10 ppm NAA. The treatment combination showing the highest average growth was BA 20 + NAA 10 ppm.Keywords : Acclimatization, BA, NAA, Phalaenopsis